O trabalhar docente com adolescentes em conflito com a lei: um olhar a partir da psicodinâmica do trabalho - Silva, Christina Pereira da (2019)
The challenge for contemporary society consists in undertaking action towards the materiality of the socio-educational proposal, in view of the goal of mediating adolescents and young people in compliance with socio-educational measures, since this policy aims to educate them for a life in freedom. This context highlights the importance of the role that should be attributed to socio-education, and especially to the teachers who work in this type of education. By taking the teaching performance in socio-educational institutions into consideration, this research has as its main goal to investigate, through the psychodynamics of work, the activities of teachers who work with adolescents in conflict with the law, in a school inserted within an internment unit in the Federal District. Specifically, we sought to analyze the organization of teaching activities based on the divergences between the prescribed and the actual work, to investigate the experiences of suffering in the teaching work and the individual and collective defensive strategies resulting from them and describe the subjective mobilizations regarding cooperative relations, recognition and practical intelligence. Methodologically, this work is a qualitative research that used, from pre-research to devolution, the work clinic as its main procedure. In light of Dejour’s theory, this method of action and intervention promoted spaces of exchange between participants and the researcher, as well as moments of collective listening, enabling us to understand individual subjective processes and collective mobilizing strategies with respect to work. The results obtained over six sessions indicated that the teaching work in the unit of study is permeated by unforeseen events and incidents, often marked by resistances to reality. Such circumstances tend to generate surprise, nervousness, irritation, and a feeling of helplessness that lead teachers to suffer. We also observed that the privileged space of discussion, promoted by the work clinic, led the participants to speak out and reduced individualism, but was not significant enough to mobilize the collectivity to implement significant changes at work. Therefore, the thesis that the subjective mobilization of teachers regarding the relationships between cooperation, recognition and practical intelligence is essential to face the difficulties of the socio-educational context was confirmed. Finally, we hope to contribute towards a detailed understanding of the way teachers work and to raise the attention of academics, politicians and society on the working conditions of teachers and their emotional and professional well-being. Also, in a broader perspective, we hope to improve the teaching work within the realm of socio-education.